Intelligent forecasting and monitoring of air index based on big data and internet of things - Yan LIU; Yong-ping ZHANG; Cheng ZHU; Jun GAO; Qi-ming LIU (Tongxin xuebao)
Air quality forecast has become an urgent need.However,numerical forecast of air quality is a complex systems engineering.The intelligent forecasting of air index was studied from the perspective of big data and intelligent decision making.For the index prediction of air quality,the popular classification algorithm was introduced to realize the intelligent analysis of historical data.To obtain air quality information in real time,a monitoring system based on Internet of Things was established,and intelligent processing of real-time data collected by the classification algorithm was achieved.Due to the large amount of historical air index data and real-time data collected,the technology of cloud computing and big data was introduced to speed up the data processing and improve the storage of data.In addition,the client based on Android was developed to allow users to query the air quality anytime,anywhere.